RESPON SISWA TERHADAP MEDIA MOBILE CHEMISTRY LEARNING BERBASIS ANDROID SEBAGAI SUPLEMEN BELAJAR MATERI HIDROKARBON - Atiq Rosyidi; A. Ifriyani Harun; Ira Lestari (Universitas Tanjungpura, 2020)
Abstract This research aims to determine students' responses to the Android-Based Mobile Chemistry Learning Media (METEROID) as a learning supplement on hydrocarbon material. Type of this research is a Research and Development (R&D) by adapting the development steps byBergman and Moore model. This response is divided into several criteria that is excellent criteria, good criteria, good enough criteria, poor criteria, bad criteria. Data collection uses a response test questionnaire, while the aspects assessed in the response test questionnaire are material aspects, appearance aspects, and aspects of expediency. Based on this research,METEROID received responses from students in the initial field response test with excellent criteria (82.06%) and the main field response test with excellent criteria (85.59%). According to the results of the students' response test to the METEROID showed that students are very good to use the METEROID media as a learning supplement for hydrocarbons material. Keywords: METEROID, mobile learning, chemistry learning, android-based, learning supplement, hydrocarbons.